Technology Integration in English as a Foreign Language Classroom: An Ethnographic Case Study of Indonesian Madrasah - Sayyidatul Fadlilah; Abdurrachman Faridi; Issy Yuliasri; Sri Wuli Fitriati (International Conference on Science, Education, and Technology, 2021)
The COVID-19 pandemic situation requires teachers to enact the distance learning which integrates technology in their English as a Foreign Language (EFL) classroom. The present study reported the experience of Secondary school English teachers at Madrasah in implementing technology in online learning of English subjects. A total of 43 English teachers in Semarang City were surveyed using G-form, 6 of them were interviewed and their online learning documents were analyzed. The interview data is coded by using Clarke & Braun's (2016) Thematic Analysis. The results showed that English teachers at madrasah had integrated technology in their EFL classroom. The challenges of using technology for the teachers are: 1) lack of supporting affordances, 2) varied learning platforms are less accessible to students, 3) lack of experience of teachers getting training and workshops 4) lack of teachers’ motivation due to low salaries, 5) teachers have another side job. From the results of the study, it is recommended that there should be training and workshop related to managing classes with technology to build teachers’ technological knowledge. For the future research, it is expected to investigate how to motivate teachers to integrate technology in their EFL classroom effectively.